The Good News Bible: Is It Good News for the Jews? Methodological Observations on Translational Choices in GNB. Issue 3 (December 2018) - Förster, Hans
In some cases the meaning-based approach used in the translation of the Good News Bible appears to support translational choices that strengthen or even introduce anti-Judaism in translation. There are instances where such translational choices are not required by the source text. It is possible, in the examples selected for discussion, to arrive at translations that follow the source text closely, are less anti-Jewish, and conform to the principles of a meaning-based approach. In principle, almost every translator of texts from the New Testament faces translational choices possibly introducing a note of anti-Judaism in translation. However, the meaning-based approach might disambiguate ambiguous passages in a way that introduces a stronger note of anti-Judaism (if compared to more formally equivalent translations), as one of the examples indicates.